INTEGRASI ILMU POLITIK DENGAN ILMU MAQASHID: PERSPEKTIF EPISTEMOLOGI ISLAM - Simamora, Nur Aisah (Universitas Islam Negeri Sumatera Utara, 2018)
One main factor wich affects Islam as backward people in this pre-civilization nowadays is some dichotomies which surge their thoughts in all aspect, such as dichotomy between sciences and approaches, dichotomy between science and Allah, humans and this universe, dichotomy between sciences and ethics, and dichotomy between sciences and it’s actualization among communities. Therefore, to re-neutralize this condition, thought sphere and islamic education sphere need a serious therapy which is termed by integration. A massive dichotomy science knowledge which is faced by moslem people with life and religion condition is politic science and politics sphere up to most of moslem community find that politic science and engage of politics are not part of worship and God knowledge. Certainly, this must a very big blunder in moslem people thought, where the politics science must be a very potential branch of conducting someone to be khairu ummah who has a great power as al-amr bi al-ma’ruf (the callers of the kindness) and an-nahyu ‘an al-munkar (the deterrents of the badness). To disenchant this blunder, and to apply the therapy of this condition, then the ideas of the knowledge integration especially politics is so crucial. Later the moslme people can see and understand how the hierarchy of all knowledge spread out from Allah, The Tranmitter of lambency (Nûr al-Anwâr), an can see the cooperative a network, duties the function of each knowledge branch.